Pelaksanaan program pemberian viamin B kompleks pada sapi potong di desa Pekalobean - Zafitrah; Puspitasari, Ita; Farid, Muhammad (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
Beef cattle are one of the meat producers that have the potential to realize Indonesia as the world's food barn by 2045. According to the expectations of the Ministry of Agriculture of the Republic of Indonesia. Indonesia will reach its golden age in 2045. The type of beef cattle in Indonesia is a cow that is adaptable and can live in the tropics. However, so far there are still obstacles in the beef cattle farming business, namely the lack of knowledge of farmers in their maintenance patterns, resulting in low production of livestock products. The determining factors for the quality of productivity are seeds, feed and livestock management. The animal feed factor dominates by 70% as a determinant of quality. Beef cattle farming is one of the contributors to protein sources. Livestock health management needs to be considered to reduce the possibility of farmers' losses due to diseases in livestock. This activity involves farmers directly in the process of injecting beef cattle. The target participants of community service activities are farmers who own cattle in Pekalobean Village. The methods used in this service activity include observation, counseling and evaluation. Livestock health management is one of the factors that directly affects the productivity of beef cattle. Optimal health in livestock is the main key to achieving maximum productivity. Therefore, livestock health care is very important. In addition to preventive efforts through maintained cage sanitation, providing vitamin supplements to livestock is also an important step to increase immunity. The administration of vitamin B complex to livestock has been proven to reduce stress and stimulate livestock growthThe program of giving vitamin B complex to beef cattle in Pekalobean village is a strategic step to improve the health and productivity of livestock. With good implementation, this program not only provides benefits for beef cattle, but also improves the welfare of farmers. It is hoped that this program can continue and become a model for other regions in an effort to improve the quality of livestock in Indonesia. Through good cooperation between the government, farmers, and the community, we can achieve a common goal in building a better livestock sector.